Tournant des politiques migratoires en Argentine - Julie Le Gall; Susana María Sassone (EchoGéo, 2008)
In a context of new presidential elections in Argentina the article analyses the changes in territorial policy within this country of the Southern Cone, in the light of migration policies adopted since the mid-2000’s. While it had always promoted European immigration, the Argentinean State is opening up to migrants from neighbouring countries and seeking to establish a policy more consistent with the migration realities of its territory, through the adoption of the Law Giustiniani (2004) and the “Patria Grande” plan (2005). The revival of the Mercosur integration process is the main engine to this opening; the new migration policy is implemented at the local and provincial level. Though this does not yet guarantee a social and economic integration process of migrants from bordering countries, the State at least acknowledges their role in building the national territory.